Surgeons, insurgents and the lost Caravaggio. Issue 1 (19th December 2017) - Ryan, É; Creavin, B; Winter, D C
Abstract: L.14702 Michelangelo Merisi da Caravaggio (1571–1610), The Taking of Christ, 1602. Oil on canvas 133·5 × 169·5 cm. On indefinite loan to the National Gallery of Ireland from the Jesuit Community, Leeson Street, Dublin, Ireland, who acknowledge the kind generosity of the late Dr Marie Lea-Wilson, 1992 (National Gallery of Ireland Collection, Photograph © National Gallery of Ireland) The Taking of Christ (c. 1602), by Italian Baroque master Michelangelo Merisi da Caravaggio (1571–1610), portrays the moment when Judas Iscariot betrays Jesus in the Garden of Gethsemane. By diminishing the environs of the three-quarter-length protagonists, and eschewing any depiction of the setting, all emphasis is concentrated on the action. The painting is perhaps the finest illustration of Caravaggio's imitable style and, like many of his paintings, it demonstrates his use of chiaroscuro . At the time of its completion, it was one of the most costly and celebrated artworks of the milieu, and would later influence other artists, generating its own style, caravaggioesque . However, just like the spectacular imagery, the provenance of the painting was for centuries shrouded in mystery, action and suspense, before a final resurrection restored its legacy. It is no surprise then that its interwoven history with the Irish medical profession and, in particular, a paediatrician, Dr Marie Lea-Wilson, is at first not obvious or well known. It was while on holiday after the assassination of her husband, a police officer, by Irish revolutionaries in the aftermath of the 1916 Easter Rising, when a number of prominent buildings around Dublin, including the Royal College of Surgeons in Ireland, were occupied, that she unknowingly bought the masterpiece. It is now on indefinite loan to the National Gallery of Ireland from the Jesuit Community of St Ignatius House of Writers, 35 Lower Leeson Street, Dublin 2, Ireland. Almost 100 years later, the story of how these events are associated with the discovery of a work of art of incalculable value has lost none of its peculiarity. Read more about the fascinating events surrounding this incredible painting in an essay online .